Study on calculation method of ecological environment flow rate of water conservancy and hydropower project in coal mining area - Dong, Ying; Wu, Xijun; Khan Chowdhury, Ahmed Jalal (Technoscience Publications, 2019)
The ecological environment is the basic natural condition related to human survival and development. Protecting and improving the ecological environment is the basis for ensuring social and economic sustainable development and a virtuous cycle of water resources, especially coal mining areas. This paper hopes to understand and master all kinds of calculation methods for the discharge of ecological flow in water conservancy and hydropower projects at home and abroad, analyse the advantages and disadvantages and application scope of various methods, and propose a more reasonable quantitative calculation method of ecological flow in combination with typical water conservancy and hydropower engineering research. The calculations show that most of the aquatic organisms have excellent habitat conditions when the river’s inner diameter flow is 60% of the average annual river flow. It is hoped that it will play a reference role for other similar water conservancy and hydropower projects in China, realize the coordination of water resources development and river ecological protection, implement ecological water conservancy and ecological hydropower model, and solve the ecological problems that restrict the development of water conservancy and hydropower in China to a certain extent.